Peroxydisulfate Co-Treatment with MnOx-Loaded Biochar for COD Removal from Automobile Service Station Wastewater - Glinsukol Suwannarat; Kunlasatree Pattanagulanan; Chonlada Rueangsukhon; Panatda Nasingthong; Chompoonut Chaiyaraksa (My University, 2022)
This research was aimed at recycling agricultural waste and treating synthetic automobile service station wastewater. Wastewater was synthesized to two levels of COD concentration: 702 mg/L (WW-A) and 7,054 mg/L (WW-B). In the treatment process, 100 mM sodium peroxydisulfate with MnOx-loaded biochar (MnOx-Biochar) was applied. The MnOx-Biochar was produced by dipping corn cob biochar in 40 mM manganese sulfate followed by pyrolyzed at 600°C. The surface area, pore volume, pore size, and pH value at the zero-point charge of MnOx-Biochar were 130 m2/g, 0.044 cm3/g, 1.02 nm, and 7.05, respectively. From the FTIR spectrogram, a peak assignable to Mn-O was observed. The results showed that the initial pH of the wastewater did not affect the treatment efficiency. The optimum MnOx-Biochar dosage was 2 g/L. Equilibrium was reached within 120 min of reaction. During the first 15 min, the treatment rate constants (k) of the WW-A and WW-B treatment were 0.0647 min-1 and 0.0349 min-1, respectively. After 15 min, the k values of the WW-A and WW-B treatments were reduced to 0.0242 min-1 and 0.0094 min-1, respectively. The overall treatment efficiencies of the low COD wastewater (WW-A) and high COD wastewater (WW-B) were 97% and 78%, respectively. The treatment mechanisms involved both adsorption and oxidation. The adsorption efficiencies of the WW-A and WW-B treatments were 36% and 18%, respectively.
Keywords: Peroxydisulfate; Water Quality Monitoring and Analysis